Hitlerś games : the 1936 Olympics - Hart-Davis, Duff 1936- (Harper & Row, 1986)
A detailed, illustrated account of the 1936 Berlin Olympic Games which ranges from the early planning from 1933 on to all key events of the games themselves, and covers the political and ideological factors involved